Studi Banding in-vitro terakit Efikasi Antelmintik Ekstrak Daun Pegagan (Centella asiatica) dan Daun Putri Malu (Mimosa pudica) terhadap Cacing Ascaris suum - Cliffton, Cliffton; Situmorang, Evi Ulina Margareta; Dewi, Rita; Joprang, Freggy Spicano (Jurnal Biomedika dan Kesehatan, 2025)
Background Nematode infections result in 60.000 deaths each year. The majority of these infections are dominated by Ascaris Lumbricoides, which is asymptomatic and is currently treated with albendazole. However, prolonged use increases the risk of drug resistance. Research on herbal anthelmintics is very much needed. Herbs like C. asiatica and M. pudica (a wild tropical plant), have proven to possess antiparasitic properties due to their anthelmintic content. Methods This research used in-vitro experiments to compare the effectiveness of M. pudica and C. asiatica herbal extracts and their concentrations on the death time of A. suum worms. Herbal extracts were obtained through remaceration techniques, and each herb was made in concentrations of 10%, 20%, and 50%. Each experimental group was given 5 A. suum worms, which were observed every hour for 24 hours. Results A total of 53.3%, 86.6%, and 93.3% of the worms died in the C. asiatica group using 10%, 20%, and 50% concentration. Meanwhile,  60%, 73.3%, and 100% of the worms died in the M. pudica group using the same concentrations. By using two-way anova to compare the effectiveness of each concentration and also to compare the two plants, it could be concluded that there was no significant difference between C. asiatica and M. pudica either in their respective concentrations (p=0.0588) or between herbs (p=0.1670). The post-hoc test carried out also showed that there was no difference in the lethal effect of the two extracts. Conclusions Both extracts exhibited similar anthelmintic effects (p > 0.05), with LC50 of 8.91% for C. asiatica and 9.33% for M. pudica.